Schizophrenia and smoking: evidence for a common neurobiological basis - Stassen, Hans H.; Bridler, R.; Hägele, S.; Hergersberg, M.; Mehmann, B.; Schinzel, A.; Weisbrod, Matthias; Scharfetter, C. (American journal of medical genetics, 2000)
Several previous investigations have suggested that the gene for the α7-nicotinic receptor may play a role in the pathogenesis of schizophrenia and may be responsible for the heavy smoking among schizophrenic patients. In a study of 129 healthy controls and 127 schizophrenic, schizoaffective, and bipolar patients we have aimed 1) to confirm the potential association between schizophrenia and the α7-nicotinic receptor, 2) to test the diagnostic specificity of α7-receptor subunits with respect to psychiatric diagnoses, and 3) to investigate potential receptor differences between smokers and nonsmokers in the general population. Our analysis included the two dinucleotide polymorphisms D15S1360 and L76630 that are localized in a genomic fragment containing the α7-nicotinic receptor gene CHRNA7. Highly significant differences (P < 0.0001) between the allele distributions of patients and controls were detected for these two markers with all three diagnostic subgroups contributing to the discrimination. An independently ascertained replication sample of 24 patients confirmed this finding. Our results suggested an unspecific vulnerability that depended on the severity of overall psychopathology in terms of the co-occurrence of psychopathology with no clear-cut boundary between the diagnostic entities. In comparison with healthy controls, this vulnerability was lowest among schizophrenics, intermediate among bipolars, and highest among schizoaffectives. As to the question of α7-receptor differences between smokers and nonsmokers among the healthy control subjects, our analysis revealed no significant differences, thus indicating that the differences between patients and controls are more than just a smoker/nonsmoker distinction. Am. J. Med. Genet. (Neuropsychiatr. Genet.) 96:173-177, 2000. © 2000 Wiley-Liss, Inc.
Gesehen am 17.11.2021